Knowledge management practices among human resource managers in private sectors in Shah Alam / Nor Farhana Mohd Azmi, Nor Hamimah Hamidun and Mahhani Musa - Mohd Azmi, Nor Farhana; Hamidun, Nor Hamimah; Musa, Mahhani (Research Management Institute (RMI), 2012)
This study focuses on a better understanding in Knowledge Management practices among Human Resource managers. Besides that this study also aims to identify whether the respondents able to apply this practices of Knowledge Management. In this context, Knowledge Management has been addressing on issues, challenges and opportunities for the private sector. As knowledge transfer is increasingly recognized as a source of value creation, organizations have come to identify Knowledge Management initiatives as strategic facilitators of competitive advantage (Xiao & Pandya, 2003). The respondents are those working as Human Resource managers who are employed in the manufacturing and service industries located in Section 2 until Section 25, Shah Alam. These respondents were chosen because the researchers feel that Human Resource Managers have their own duties and responsibilities to ensure the knowledge management practices successfully applied. The study has revealed that majority of respondents did agreed that Knowledge Management Practices is important in order to increase productivity and quality of the organization.